Guidelines for Nonvariceal Upper Gastrointestinal Bleeding - Kim, Joon Sung (Gut Liver, 2020)
Nonvariceal upper gastrointestinal bleeding (NVUGIB) refers to bleeding that develops in the gastrointestinal tract proximal to the ligament of Treitz. NVUGIB requires hospitalization and is associated with significant morbidity and mortality. Although European and Asian-Pacific guidelines have been published, there have been no previous guidelines regarding management of NVUGIB in Korea. Korea has a high prevalence of Helicobacter pylori infections, and patients have easy accessibility to endoscopy. Therefore, we believe that guidelines regarding management of NVUGIB in Korea are essential. The Korean Society of Gastroenterology reviewed the recent evidence and recommends practical management guidelines on NVUGIB in Korea.